Why do mothers from remote rural areas opt for cesarean delivery: An observational analytical study from West Bengal, India - Farhad Ahamed; Tanveer Rehman; Amandeep Kaur (Wolters Kluwer Medknow Publications, 2023)
Background: The percentage of cesarean section (C-section) deliveries has doubled in the last two decades in India. Although C-section delivery is a life-saving intervention, multiple maternal and neonatal morbidities are often associated with this procedure, adversely affecting the quality of life of both the mother and child. Material and Methods: This community-based cross-sectional study was conducted to assess the point of view of mothers who delivered from January 2020 to June 2021. Results: The mean (standard deviation (SD)) age of the 866 study participants at delivery was 24.5 (4.8) years, and 60.2% were primigravidas. A total of 613 (70.8%; 95% CI: 67.8-73.8) C-sections were conducted, of which 65.9% (n = 404) were planned and 21.9% were done on maternal request. C-sections were significantly associated with private institutes (adjusted prevalence ratio (aPR) 1.90; 95% CI: 1.70-2.11), at-risk pregnancy (aPR 1.37; 95% CI: 1.26-1.49), and primigravida (aPR 1.16; 95% CI: 1.05-1.29). About 55.3%, 29.8%, and 14.9% of women considered vaginal delivery to be risky, painful, and inconvenient, respectively. Conclusion: It is imperative to generate awareness regarding modes of delivery during antenatal care (ANC) so that mothers can make better-informed choices.